Heart failure and cognitive impairment: A narrative review of neuroimaging mechanism from the perspective of brain MRI - Li, Tong; Bao, Xiangyuan; Li, Lin; Qin, Rui; Li, Cuicui; Wang, Ximing (Frontiers in Neuroscience, 2023)
Normal brain function is typically impaired by heart failure (HF) in the form of decreased cerebral perfusion pressure, inflammation, oxidative stress, and damage to the blood-brain barrier, resulting in cognitive impairment (CI) and subsequent HF. Magnetic resonance imaging (MRI) can noninvasively detect functional and structural variations in the heart and brain, making it easier to explore the connection between heart and brain. English-language literature were searched in Web of Science, PubMed EMBASE (OVID), PsycInfo, and Scopus databases. The search terms include "high-frequency," "brain function," "brain injury," "cognition," "cognitive dysfunction," and "magnetic resonance imaging." This review describes the pathogenesis of HF with cognitive dysfunction and the early diagnostic role of MRI in the heart-brain domain.